Pengaruh Disiplin Kerja dan Self Efficacy terhadap Kinerja Karyawan Dengan Gaya kepemimpinan Sebagai Variabel Interveing (Pada Karyawan Sekretariat DPRD Bangkalan) - Dita Ayu Anggraini; Iriani Ismail (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine the effect of work discipline and self-efficacy on employees performance and leadership style directly and indirectly at the DPRD Secretariat, Bangkalan. It used a non-probability sampling technique and as many as 98 employees to be used as samples.Using the path analysis, the results showed that (1) Work discipline has a negative and significant effect on employees performance (-0.472). (2) Self-efficacy has a positive and significant effect on employees performance (0.755). (3) Work discipline has a positive and significant effect on leadership style (0.497). (4) Self efficacy has a positive and significant effect on leadership style (0.483). (5) Leadership style has a positive and significant effect on employees performance (0.661). (6) Work discipline has a positive and significant indirect effect on employees performance through the leadership style as intervening variable (0.328). (7) Self-efficacy has a positive and significant indirect effect on employees performance through the leadership style as intervening variable (0.319). It is lower than the effect of self-efficacy on employees performance directly (0.775).